Editorial: Whither globalization and health in an era of geopolitical uncertainty? - Ronald Labonté; Greg Martin; Katerini T. Storeng (BMC, 2022)
Abstract Globalization has been declared dead or dying for many years, although recently, the number of voices declaring it 'over' has swelled [1]. As editors of a journal interrogating how globalization affects health, we confront the question: Have the COVID-19 pandemic, Russia's war against Ukraine, a breakdown in multilateralism, and the risk of a return to the stagflation of the 1970s finally sounded a death knell for the research and scholarship we have been publishing in the journal's 20-year history? We think not and argue below why, in our post-pandemic fractured and fractious era, it is vitally important to retain a focus on this messy construct short-handed as 'globalization.'